Unwelcome Immigrants: Sources of Opposition to Different Immigrant Groups Among Europeans - Gorodzeisky, Anastasia; Semyonov, Moshe (Frontiers in Sociology, 2019)
The present paper advances the proposition that level of opposition to immigration (i.e. endorsement of closure or exclusion) and its sources are not uniform and vary across immigrant groups. To test this proposition we utilize data from the 2014 European Social Survey for 20 countries and apply the analysis to the following groups: immigrants of same race/ethnic group as a majority population, immigrants of different race/ethnic group, Muslim, Jews and Roma immigrants. The analysis reveals that level of opposition to immigration of different ethno-religious groups in Europe is hierarchical, being most extreme toward Muslims and Roma and quite minor toward people of the same ethnic/race groups as well as toward Jews. Further analysis reveals that not only the level of opposition varies across groups but also the sources that drive such opposition. In general, the sources of opposition to immigration can be divided to two major categories: universal sources and group-specific sources. The universal sources (sources which increase opposition toward all immigrants regardless of their origin) pertain to threat of competition over socio-economic and symbolic resources. The group-specific sources consist of racism, fear of crime and inter-group contact. Racism and lack of inter-group contact tend to increase opposition that is exclusive to Muslim and to Roma immigrants. Racism, however, does not increase opposition that is exclusive to immigrants belonging to a race/ethnicity, which is different from most country people. Fear of crime is likely to prompt opposition that is exclusive to immigrants of different race/ethnic group and to Roma but not toward Muslims. The findings underscore the multiple sources underlying emergence of anti-immigrant sentiment, in general, and opposition to specific groups of immigrants, in particular.